Unconventional vegetables collected in Brazil: chromosome number and description of nuclear DNA content - Silva,Luis Felipe Lima e (2017)
Abstract The aim of this study was to perform chromosome counts and nuclear DNA quantification of the unconventional vegetables species: bertalha (Basella alba L.), vinagreira verde (Hibiscus sabdariffa L.), azedinha (Rumex acetosa L.), peixinho (Stachys byzantina K. Koch), and capuchinha (Tropaeolum majus L.). Metaphase chromosomes were obtained from the pre-treatment of root meristem with 8-hydroxyquinoline or colchicine and lides were prepared by the flame-drying technique and stained with 5% Giemsa. DNA quantification was performed by flow cytometry. Chromosome number and DNA content (pg) estimated for each species were: Rumex acetosa: 2n=2x=14 and 7.04 pg; Basella alba: 2n=2x=44 and 7.05 pg; Tropaeolum majus: 2n=2x=28 and 2.08 pg; Stachys byzantine: 2n=2x=30 and 1.54 pg, and Hibiscus sabdariffa: 2n=4x=72 and 5.12 pg.